Immune contexture and histological response after neoadjuvant chemotherapy predict clinical outcome of lung cancer patients. (1st December 2016) - Remark, Romain; Lupo, Audrey; Alifano, Marco; Biton, Jerome; Ouakrim, Hanane; Stefani, Alessandro; Cremer, Isabelle; Goc, Jeremy; Régnard, Jean-Francois; Dieu-Nosjean, Marie-Caroline; Damotte, Diane
ABSTRACT: There is now growing evidence that the immune contexture influences cancer progression and clinical outcome of patients with non-small cell lung cancer (NSCLC). If chemotherapy is widely used to treat patients with advanced-stage NSCLC, it remains unclear how it could modify the immune contexture and impact its prognostic value. Here, we analyzed two retrospective cohorts, respectively composed of 122 stage III-N2 NSCLC patients treated with chemotherapy before surgery and 39 stage-matched patients treated by surgery only. In patients treated with neoadjuvant chemotherapy, the histological characteristics, the expression of PD-L1 protein, and the tumor immune microenvironment (CD8 + T cells, DC-LAMP + mature dendritic cells, and CD68 + macrophages) were evaluated and their prognostic value assessed together with standard clinical parameters. By analyzing pre- and post-treatment specimens, we did not find any changes in the PD-L1 expression. We also found that the tumor immune contexture in patients treated with neoadjuvant chemotherapy exhibited a similar pattern that the one found in chemotherapy-naive patients, with comparable densities of tumor-infiltrating CD8 + and DC-LAMP + cells and a similar spatial organization. The percentage of residual viable tumor cells and the immune pattern (CD8 + and DC-LAMP + cell densities) were significantly associated with the clinical outcome and allowed the identification of short- and long-term survivors, respectively. In multivariate analysis, the immune pattern was found to be the strongest independent prognostic factor. In conclusion, this study decrypts the complex interplay between cancer and immune cells in patients undergoing chemotherapy and supports potential beneficial synergistic effect of immunotherapy and chemotherapy.